Health Counseling to Enhance Maternal Knowledge about Nutrition in Toddlers - Liena - Sofiana; Arfiani Nur Khusna (International Journal of Healthcare Research, 2018)
Background: The level of maternal knowledge about high nutrition can affect the diet of baby and will certainly affect nutritional status of toddlers. The knowledge can be generated from several ways, one of them is counseling. Counseling is one method can be used easily to provide the knowledge about the nutrition of toddlers to mothers.Objective: The purpose of this study is to determine the effect of health counseling about nutrition of toddlers on mothers in the posyandu Kauman Yogyakarta.Methodology: This study used quasy experimental with pretest and posttest. The populations in this study include all mothers of children who came to the posyandu Kauman Yogyakarta with the sampling technique with total sample are 26 respondents. The processing data used the Wilcoxon test because the data is not normally distributed.Results: The results shows that there is an effect of health counseling in increasing maternal knowledge about nutrition of baby in Kauman Yogyakarta posyandu (p = 0.000).Conclusion: there is an effect of health counseling in increasing maternal knowledge about nutrition of children in posyandu Kauman Yogyakarta.